Modification of the Inner Part of the Oil Palm Trunk (OPT) with Oil Palm Shell (OPS) Nanoparticles and Phenol Formaldehyde (PF) Resin: Physical, Mechanical, and Thermal Properties - Md Nazrul Islam; Y. Davoudpour; Alfi Rumidatul; H. P. S. Abdul Khalil (BioResources, 2013)
This study was conducted to enhance the physical, mechanical, and thermal properties of the inner part of the oil palm trunk (IP-OPT) impregnated with oil palm shell (OPS) nanoparticles at various concentrations (0, 1, 3, 5, and 10%) and phenol formaldehyde (PF) resin. The PF concentration was 15% (w/w basis) throughout the study. The physical, mechanical, and thermal properties of the OPS nanoparticle-impregnated IP-OPT lumber were analyzed according to various standards. It was found that IP-OPT gained a significant percentage of weight (up to 35.3%) due to the treatment, leading to a density increase from 0.42 to 0.89 g/cm3. The water absorption was reduced by up to 24%, which reduced the swelling coefficient, and thus, the anti-swelling efficiency was increased significantly. The tensile and flexural strengths increased from 9.77 to 19.64 MPa and from 14.46 to 38.55 MPa, respectively. The tensile and flexural moduli increased from 2.67 to 3.51 GPa and from 4.35 to 4.95 GPa, respectively, while the elongation at break decreased from 7.83 to 6.42%. The impact strength also increased significantly, from 6.90 to 15.85 kJ/m2. In addition, the thermal stability of IP-OPT was improved by the impregnation of OPS nanoparticles. Thus, it can be concluded that the impregnation of IP-OPT with OPS nanoparticles might be a good treatment process for enhancing the properties of the IP-OPT.